2023
DOI: 10.3389/fendo.2023.1183161
|View full text |Cite
|
Sign up to set email alerts
|

Captopril challenge test in the diagnosis of primary aldosteronism: consistency between 1- and 2- h sampling

Abstract: ObjectiveTo examine the consistency of plasma aldosterone concentration at 1 and 2 h in the captopril challenge test (CCT) and to explore the possibility of replacing 2-h aldosterone concentration with 1-h aldosterone concentration for diagnosis of primary aldosteronism (PA).MethodsThis retrospective analysis included a total of 204 hypertensive patients suspected of having PA. Subjects received oral captopril challenge at 50 mg (25 mg if the systolic blood pressure was <120 mmHg), and plasma aldosteron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The diagnostic performance of the 1-h aldosterone concentration was assessed by sensitivity and specificity, using the 2-h aldosterone concentration (11 ng/dL as the cutoff) as the reference. Receiver operating characteristic (ROC) curve analysis was also performed ( 39 ).…”
Section: Protocols For Cct and Outcome Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic performance of the 1-h aldosterone concentration was assessed by sensitivity and specificity, using the 2-h aldosterone concentration (11 ng/dL as the cutoff) as the reference. Receiver operating characteristic (ROC) curve analysis was also performed ( 39 ).…”
Section: Protocols For Cct and Outcome Evaluationmentioning
confidence: 99%
“…Conversely, a lower cutoff of 9.3 ng/mL increased sensitivity to 97.9% but decreased specificity to 65.4%. The authors concluded that when diagnosing PA with a captopril challenge, the 1-h aldosterone concentration cannot be used as a substitute for the 2-h aldosterone concentration ( 39 ).…”
Section: Protocols For Cct and Outcome Evaluationmentioning
confidence: 99%